Uninephrectomy and sodium‐glucose cotransporter 2 inhibitor administration delay the onset of hyperglycemia - Yuri Sakai Ishizaki; Masao Kikuchi; Koichi Kaikita; Shouichi Fujimoto (Physiological Reports)
Abstract The kidneys are essential for glucose homeostasis, as they perform gluconeogenesis, utilize glucose, and reabsorb glucose. Reabsorption is performed by SGLT2, which is responsible for about 90%. However, little is known about how renal glucose handling is altered in patients with chronic kidney disease (CKD). SGLT2 inhibitors have demonstrated efficacy in suppressing CKD progression in clinical trials, but their mechanisms are not fully understood. Therefore, this study aimed to evaluate how each uninephrectomy (UNx) and SGLT2 inhibitor affects blood glucose concentrations and SGLTs dynamics in rats with type 2 diabetes mellitus. Male rats were divided into four treatment groups: sham + placebo, sham + dapagliflozin, UNx + placebo, and UNx + dapagliflozin. There were few group differences in food intake or body weight, but blood glucose concentrations continued to rise in the sham + placebo, whereas this rise was delayed for several weeks in the UNx + placebo, and largely suppressed by dapagliflozin. SGLT2 mRNA expression was significantly lower in the UNx group, but SGLT1 mRNA expression did not significantly differ. Dapagliflozin did not alter SGLT1 or SGLT2 mRNA expression. In animal models of diabetes, renal glucose reabsorption appears likely to be a major contributor to the development of hyperglycemia.